PROSES BERPIKIR SISWA DALAM MEMECAHKAN MASALAH NON-RUTIN PADA FASE REACTING, COMPARING, DAN CONTEMPLATING - Iksanti, Aliana; Kartikasari, Christina (HISTOGRAM: Jurnal Pendidikan Matematika, 2023)
Reflective thinking begins with repeated confusion experienced by students and then an evaluation is carried out to be able to solve the problem. In reflective thinking there are reacting, comparing, and contemplating phases. This study aims to describe students’ thinking skills in solving non-routine problems in the reacting, comparing, and contemplating phases. This study used a qualitative descriptive method with 30 class IX junior high school students as subjects. The data sources for this research were entirely obtained from the results of non-routine test questions and student interviews. The results showed that students with high-level mathematical abilities were able to fulfill the indicators of reflective thinking in the three phases, students with low-level mathematical abilities were also able to fulfill the indicators of reflective thinking in the reacting, comparing and contemplating phases while students with low-level reflective thinking abilities were only able to fulfill the indicators reflective thinking in the reacting phase.